1983
DOI: 10.1029/ja088ia09p06944
|View full text |Cite
|
Sign up to set email alerts
|

Low‐energy (<100 eV) ion pitch angle distributions in the magnetosphere by ISEE 1

Abstract: Low‐energy (<100 eV) ion data from the plasma composition experiment on ISEE 1 are examined statistically to study pitch angle distributions in all local times of the magnetosphere (L = 3–10). The pitch angle distributions in the data set used here can be classified into seven types; however, there are four major types, i.e., isotropic distribution, bi‐directional field‐aligned distribution, unidirectional field‐aligned distribution, and low flux. The isotropic distribution that consists of very low energy (ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 59 publications
8
41
1
Order By: Relevance
“…Early measurements with the Dynamics Explorer of the midqatitude plasmapause crossings in the bulge region show that the crossings occur at lower L values than the equatorial plasmapause crossings determined with OGO 5 data [Chappell, 1982]. The presence of trapped plasma at the equator as shown in this work and by Horwitz and Chappell [1979] and the absence of trapped plasma in ISEE 1 observations at higher latitudes as reported by Nagai et al [ 1983 ] suggest that the ionosphere and the equatorial bulge region, or parts of it, may actually be disconnected rather than just topologically separated. This would suggest at the least a topological separation of ionospheric plasma and the equatorial bulge region plasma.…”
Section: Into the Local Time Region Where It Is Seen On Day 46supporting
confidence: 62%
“…Early measurements with the Dynamics Explorer of the midqatitude plasmapause crossings in the bulge region show that the crossings occur at lower L values than the equatorial plasmapause crossings determined with OGO 5 data [Chappell, 1982]. The presence of trapped plasma at the equator as shown in this work and by Horwitz and Chappell [1979] and the absence of trapped plasma in ISEE 1 observations at higher latitudes as reported by Nagai et al [ 1983 ] suggest that the ionosphere and the equatorial bulge region, or parts of it, may actually be disconnected rather than just topologically separated. This would suggest at the least a topological separation of ionospheric plasma and the equatorial bulge region plasma.…”
Section: Into the Local Time Region Where It Is Seen On Day 46supporting
confidence: 62%
“…There are, however, reports of bi-directional ion conic distributions on closed field lines at Earth. Nagai et al (1983) and Sagawa et al (1987) reported bi-directional ion distributions on closed field lines near and equtorward of the auroral zone with morphology similar to the bi-directional electron distributions seen at Mars. These ion distributions are seen in both H + and O + ions primarily on the dawn side of the magnetosphere on auroral field lines.…”
Section: Discussionmentioning
confidence: 61%
“…Note that the occurrence probabilities in the morning to afternoon sector are in the 50–100% range with the routine occurrence level of >80% in the prenoon region. Nagai et al [1983] found that the bidirectional distributions' occurrence probability increased with decreasing Kp in contrast to the unidirectional field‐aligned distributions seen on the nightside at higher L shells. Even though its occurrence probability varies with magnetic activity this distribution is a persistent feature of the outer prenoon region in both quiet and active times.…”
Section: Observations Related To the Warm Plasma Cloakmentioning
confidence: 69%
“…Magnetic activity was low during this survey, with over 88% of the data acquired while Kp was less than or equal to 3. Since the ISEE survey (see Figure 1) took place 22 years earlier, our observations fell during the same portion of the solar cycle as those published by Nagai et al [1983].…”
Section: Tide Occurrence Probabilities Of Bidirectional Field‐alignedmentioning
confidence: 81%
See 1 more Smart Citation